Clinical Features and Risk Factors for Lymph Node Metastasis in Early Signet Ring Cell Gastric Cancer - Jin, Xiaoliang; Wu, Wei; Zhao, Jing; Song, Shuang; Zhang, Chunli; Sun, Wenyong; Lv, Bin (Frontiers in Oncology, 2021)
Signet ring cell carcinoma (SRCC) was previously thought to have a worse prognosis than differentiated gastric carcinoma (DC). However, recent studies have shown that its prognosis is related to staging. Here, we analyzed the clinicopathological features and the rate of lymph node metastasis (LNM) in 2166 patients with gastric cancer (605 early and 1561 advanced cases) who underwent gastrectomy and lymph node dissection (D2) from 2016 to 2019. The LNM rate for early and advanced cases was 18.0% and 74.2%, respectively. Regarding early cases, the LNM rate in SRCC was similar to that in DC (10% vs. 16.1%, p=0.224), and significantly lower than that in undifferentiated carcinoma (UDC; 10% vs. 23.3%, p=0.024). Tumor size, infiltration depth, pathological type, and mixed type were risk factors for LNM in early cases. Regarding intramucosal cases, the LNM rate in SRCC was similar to that in DC (4.3% vs. 3.7%, p=0.852), and significantly lower than that in UDC (11.2%). The LNM rate was significantly higher in submucosal than intramucosal cases (28.1% vs. 6.3%, p<0.001), and in early mixed cases than early pure cases (23.2% vs. 12.4%, p<0.001). Regarding early pure cases, the LNM rate in SRCC was similar to that in DC (9.3% vs. 7.2%, p=0.641), but significantly lower than that in UDC (9.3% vs. 24.7%, p=0.039). In summary, the LNM rate in early SRCC was similar to that in early DC but significantly lower than that in early UDC. Early SRCC fits with the endoscopic submucosal dissection (ESD) indication related to undifferentiated cases, and ESD may be effective. Additionally, the LNM rate was markedly higher for submucosal cases than intramucosal cases, and for mixed cases than pure cases.